The 8q24 Gene Desert: An Oasis of Non-Coding Transcriptional Activity - Huppi, Konrad; Pitt, Jason J.; Wahlberg, Brady M.; Caplen, Natasha J. (Frontiers in Genetics, 2012)
Understanding the functional effects of the wide-range of aberrant genetic characteristics associated with the human chromosome 8q24 region in cancer remains daunting due to the complexity of the locus. The most logical target for study remains the MYC protooncogene, a prominent resident of 8q24 that was first identified more than a quarter of a century ago. However, many of the amplifications, translocation breakpoints and viral integration sites associated with 8q24 are often found throughout large regions surrounding the MYC locus and often include other loci. In addition, Chr. 8q24 is host to a number of SNPs associated with cancer risk. Yet, the lack of a direct correlation between cancer risk alleles and MYC expression has also raised the specter of doubt that MYC is the sole target of these genetic associations. The 8q24 region has been described as a “gene desert” because of the paucity of functionally annotated genes located within this region. In this review, we examine the current evidence for the involvement of other loci within the 8q24 region, most of which are non-coding transcripts, either in concert with MYC or independent of MYC, as possible candidate gene targets in malignancy.